Hemodializuojamų pacientų slaugos ir sveikatos problemos - Brazaitytė, Reda; Burneikaitė, Guoda (Slauga. Mokslas ir praktika, 2022)
Proper hemodialysis management eliminates the toxic substances that are accumulated in the patient's blood due to kidney failure. Patients undergoing and requiring hemodialysis face many nursing and health problems such as nausea, vomiting, decreased appetite, shortness of breath, changes in blood pressure, pain, risk of infection, depression, obstipation, and other problems. Hemodialysis is not just a procedure, but a lifestyle changes in daily routine for a patient. Nurses’ role is very important to identify and manage nursing and health problems.
Keywords: hemodialysis; patients; nursing; nursing problems